OPERATIONAL MANAGEMENT OF SASAK FISH LANDING BASE,PASAMANBARAT DISTRICT WESTSUMATERA - Risa Miswara; Alit Hindri Yani; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research was conducted in July 2019 at the Sasak Fish Landing Base.Thepurposeofthestudywastofindoutoperationalmanagementandtheproblems that exist in the SasakFishLanding Base,especially regarding theelementsandapplicationofmanagementfunctionsinitsmanagement.Themethod used in this research is a survey method. Management data analysis wascarriedout descriptivelyand SWOT analysis.The facilities owned by PPI Sasak are basic facilities, namely docks, portland, port pools, complex roads, functional facilities owned are TPI while forsupportingfacilities owned areport offices andsecurityposts /guard postsThestrategyindevelopingtheSasakPPIintheoperationalmanagementoftheSasakFishLandingBaseisSO(Strengths-Opportunities),Thisisafavorable situation, because this strategy has strengths and opportunities, namelyby utilizing all strengths to obtain maximum opportunities in the development oftheSasak FishLandingBase.Based on the results of the Likert scale weighting for the satisfaction leveloffishermenwiththeservicequalityofPPISasakoperationalmanagement,which is 161.9 or 98.075%, the satisfaction level of the best Sasak PPI fishermenisin the categoryclose toSB(VeryGood).Keywords:Operational Management,SWOTanalysis,PPISasak